Advances in Heat and Mass Transfer in Micro/Nano Systems - Zhang, Junfeng; Wang, Ruijin (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The miniaturization of components in mechanical and electronic equipment has been the driving force for the fast development of micro/nanosystems. Heat and mass transfer are crucial processes in such systems, and they have attracted great interest in recent years. Tremendous effort, in terms of theoretical analyses, experimental measurements, numerical simulation, and practical applications, has been devoted to improve our understanding of complex heat and mass transfer processes and behaviors in such micro/nanosystems. This Special Issue is dedicated to showcasing recent advances in heat and mass transfer in micro- and nanosystems, with particular focus on the development of new models and theories, the employment of new experimental techniques, the adoption of new computational methods, and the design of novel micro/nanodevices. Thirteen articles have been published after peer-review evaluations, and these articles cover a wide spectrum of active research in the frontiers of micro/nanosystems.